The Role of Human Resources Education in Improving the Competence and Commitment of Health Cadres in the Community - Salsabila A R, Anisah; Sipatu, Lindanur; Adam, Rosida; Kurniawan, Arie (Journal of Educational Management Research, 2025)
This study aims to analyze the role of Human Resources (HR) education in improving the competence and commitment of health cadres. Using a qualitative case study design, this study involved six health cadres and three service recipients as informants. Data were collected through in-depth interviews, observations, and documentation, and analyzed using NVivo 12 Plus. The results of the study show that health cadres have a high level of commitment, both in terms of affective, sustainable, and normative commitments, despite limited facilities and suboptimal rewards. The community recognizes the important role of cadres in maintaining their health, but there is a real need to improve cadres' medical knowledge and technical skills. Human resource education has been proven to improve cadre competence, but continuous training and facility improvements are still needed to support cadre performance. This study identifies that a positive attitude of cadres, openness to criticism, and good social relations with the community are key factors in improving the quality of health services. The implications of these findings are the importance of a more structured HR education strategy and adequate facility support to ensure sustainability and optimal quality of health services at the community level.